Indirect costs of chronic N18 kidney disease in Poland - Koc, Martyna; Szumiał, Szymon; Czerw, Aleksandra Izabela (Journal of Education, Health and Sport, 2019)
The article presents the estimation of indirect costs of chronic N18 kidney disease in Poland. Research methods: The presented estimates were based on the human capital method. They concern the costs of absenteeism, presenteeism, informal care, permanent or temporary incapacity to work and deaths. Results: The total indirect cost of chronic renal failure was 281,134,988,528.50 PLN. Conclusions: The indirect costs of chronic kidney disease in Poland are high, especially in terms of presenteeism. This result is consistent with the data obtained in other countries. Building cost awareness and enabling patients to be professionally active with flexible work schedules seem to be particularly important. The availability of more accurate data would allow for more accurate estimates of indirect costs of CKD and other chronic diseases in the future.